Race and place at the city limits: imaginative geographies of South Central Los Angeles. Issue 14 (13th November 2016) - Wiggins, Benjamin
ABSTRACT: In the early 1990s, a new cycle of films emerged that depicted complex portrayals of the lives of African-Americans in the neighbourhoods in which they lived. This so-called 'hood genre was quite radical in its foregrounding of structural racism and police violence. But Hollywood's marketing of these films muted this radical content by directly contradicting explicit signifiers in the films' story worlds. While many of the 'hood films take place on the urban fringe and in suburbs, their promotional materials worked to confine the action, to a mythic 'inner city'. This essay studies the two most popular films of the genre, Boyz n the Hood and Menace II Society, to illustrate how 'paratexts' redistricted 'hood films. Through a comparative analysis of the films and their promotional materials, this essay argues Hollywood marketed a racialized 'imaginative geography' for this important genre of African-American cinema.